Stereocontrolled 1,3-nitrogen migration to access chiral α-amino acids - Ye, Chen-Xi (Nat Chem, 2022)
α-Amino acids are essential for life as building blocks of proteins and components of diverse natural molecules. In both industry and academia, the incorporation of unnatural amino acids is often desirable for modulating chemical, physical, and pharmaceutical properties. We here report a protocol for the economical and practical synthesis of optically active α-amino acids based on an unprecedented stereocontrolled 1,3-nitrogen shift. Our method employs abundant and easily accessible carboxylic acids as starting materials, which are first connected to a nitrogenation reagent, followed by a highly regio- and enantioselective ruthenium- or iron-catalyzed C(sp(3))−H amination. This straightforward method displays a very broad scope, providing rapid access to optically active α-amino acids with aryl, allyl, propargyl, and alkyl side chains, and also permits stereocontrolled late-stage amination of carboxylic acid-containing drugs and natural products. [Image: see text]